Stability Calculation Method of Slope Reinforced by Prestressed Anchor in Process of Excavation - Zhong Li; Jia Wei; Jun Yang (The Scientific World Journal)
This paper takes the effect of supporting structure and anchor on the slope stability of the excavation process into consideration; the stability calculation model is presented for the slope reinforced by prestressed anchor and grillage beam, and the dynamic search model of the critical slip surface also is put forward. The calculation model of the optimal stability solution of each anchor tension of the whole process is also given out, through which the real-time analysis and checking of slope stability in the process of excavation can be realized. The calculation examples indicate that the slope stability is changed with the dynamic change of the design parameters of anchor and grillage beam. So it is relatively more accurate and reasonable by using dynamic search model to determine the critical slip surface of the slope reinforced by prestressed anchor and grillage beam. Through the relationships of each anchor layout and the slope height of various stages of excavation, and the optimal stability solution of prestressed bolt tension design value in various excavation stages can be obtained. The arrangement of its prestressed anchor force reflects that the layout of the lower part of bolt and the calculation of slope reinforcement is in line with the actual. These indicate that the method is reasonable and practical.